AB0042 Natural Autoantibodies Against Citrate Synthase and DNA Topoisomerase I in Patients with Rheumatoid Arthritis and Spondyloarthritis Receiving Anti-TNF-α Therapy. (9th June 2015) - Simon, D.; Pusztai, A.; Najbauer, J.; Németh, P.; Szekanecz, Z.; Berki, T.
Abstract : Background: Natural autoantibodies bind to evolutionarily conserved antigens in organs and tissues of the body and may have regulatory functions in the immune system and play a role in the clearance of apoptotic cells. It has been known that some patients treated with anti-TNF-α agents develop autoantibodies, including antinuclear and anti-double-stranded DNA antibodies. However, in patients with rheumatoid arthritis (RA) and spondyloarthritis (SpA) treated with TNF-α blockers there have been no studies regarding the presence of natural autoantibodies against citrate synthase (CS), a mitochondrial inner membrane enzyme, and DNA topoisomerase I (topo I), an enzyme that relaxes the superhelical stress in DNA. Objectives: Our aim was: (1) to investigate whether patients with RA and SpA receiving anti-TNF-α treatment produce natural autoantibodies to CS and topo I; and (2) to test whether such therapy affects the levels of these autoantibodies. Methods: The study included a total of 36 patients (20 with RA, 16 with SpA) who received certolizumab or etanercept therapy. The levels of anti-CS and anti-topo I (immunodominant fragment) autoantibodies (IgM and IgG) were measured in the blood serum using enzyme-linked immunosorbent assay developed in our laboratory. The measurements were done at the starting point (0), 6, or 12 months of therapy. Results: In the combined patient group (RA + SpA) we detected significantly increased levels of anti-CS IgM and IgG antibodies after 6 and 12 months of anti-TNF-α therapy. The anti-topo I IgM and IgG were significantly elevated only after 12 months of therapy, when compared to baseline antibody levels before the start of treatment. Conclusions: The significance of the presence of anti-CS and anti-topo I natural autoantibodies is still a subject of research. We hypothesize that the increase in the levels of these natural autoantibodies might be a marker for the functional role of the natural immune system in patients treated with anti-TNF-α blockers. Because TNF-α is a pleiotropic cytokine, blocking its function can elicit various side-effects, including hematological, immunological, and others. Natural autoantibodies may function in the clearance of apoptotic cells and they may help restore the immunological milieu by reducing inflammation and protecting against some infections, functions in which the natural immune system has been implicated. Disclosure of Interest: None declared